Evolutionary design framework for Smart PSS: Service engineering approach. (August 2020) - Watanabe, Kentaro; Okuma, Takashi; Takenaka, Takeshi
Abstract: Digital technology is transforming industry, economy, and society. Under this digitalization trend, a new concept of product and service offerings, Smart PSS has been introduced. While the Smart PSS concept aiming at data-driven innovation attracts more attentions, there are two major challenges in designing Smart PSS. First, available data from digital technologies are actually limited by technical, financial, and social reasons. Second, the context of applying Smart PSS dynamically changes, which makes designed Smart PSS unfit to the target situation. To overcome these challenges, we propose an evolutionary design framework for Smart PSS. Our approach is based on the service engineering research, which has been contributing to the design and development of PSS. The proposed framework consists of three conceptual spaces and three cycles. The main features of the framework were two design cycles; in-system and ex-system design cycle. In-system design cycle is a process of creating and applying human knowledge for making the most use of data collected by digital technologies. Ex-system design cycle is to adapt to dynamic changes in contexts of the applied Smart PSS. We examine how the proposed framework works for designing a Smart PSS, with a case study about the digitalization of a restaurant business.